Glass Half-Full or Half-Empty? A Fire-Resistant Species Triggers Divergent Regeneration in Low-Resilience Pastures - Sánchez-Tapia, Andrea; Sansevero, Jerônimo Boelsums Barreto; Garbin, Mário Luís; Braga, João Marcelo Alvarenga; Figueiredo, Pablo Hugo Alves; Scarano, Fabio Rubio (Frontiers in Forests and Global Change, 2020)
Fire may divert or arrest natural regeneration in abandoned pastures throughout the tropics, transforming them low-resilience systems that do not recover even in the absence of disturbances. Understanding regeneration in degraded landscapes is crucial to decision-making and predicting the outcome of passive or active restoration actions. We aimed to understand the effects of intensifying fire regimes on post-fire natural regeneration in sites degraded by logging and fire in the Brazilian Atlantic Forest. We studied five areas with different fire regimes, (i.e., different fire frequencies and post-fire regeneration time), dominated by Moquiniastrum polymorphum (Asteraceae), a widely-distributed species with fire resistance traits. We analyzed differences in structure, diversity, the amplitude of the species' geographic distribution, and floristic composition. We recorded Leaf Area Index and grass cover to understand the effect of canopy closure on fire exclusion and analyzed functional traits related to succession and response to fire (specific leaf area, height, wood density, bark thickness, seed mass). Post-fire regeneration was slow and fire-prone and dominance by M. polymorphum decreased with less disturbance, as other species entered the communities. Structure, diversity, and functional composition recovered along the gradient but did not reach old-growth values. The taxonomic composition was strikingly different in burned areas and forests, irrespective of fire history. Natural regeneration followed a divergent trajectory, marked by the establishment of other widely-distributed species, which suggests a long-term floristic impoverishment. The establishment of M. polymorphum allows these pastures to exit grass-fire cycles. Longer post-fire recovery and fewer fire events allow for canopy closure, grass exclusion, and eventually fire suppression. This two-step dynamic breaks a crucial barrier for restoration from degraded pastures and represents a more desirable state than pastures. However, relying only upon natural regeneration results in impoverished secondary forests. Given the pervasive effects of deforestation and fire, natural regeneration observed in tropical landscapes may correspond to impoverished new secondary forests that fail to attain conservation targets for the biome. Preventing future fires and controlling grass cover in the understory is crucial to avoid their retrogression to pastures and to treat them as regeneration templates for active restoration.